The Management of Madrasah Head in Empowering of State Madrasah Educators in Jambi Province - T, Dahlia; Maisah, Maisah; Lukman Hakim (Dinasti Publisher, 2024)
This research aims to analyze and evaluate the management of madrasah heads in empowering teaching staff in an effort to minimize the gaps that occur due to the unequal placement of teaching staff. This research is qualitative research with data collection techniques using observation and direct interviews, namely MAN 1 Jambi City, MAN 1 Muaro Jambi and MAN 1 Batanghari. The data analysis technique uses qualitative through domain, taxonomy and component analysis, and the data is reduced, displayed and summarized. The research results show that (1) the correct, orderly, accurate and systematic planning of madrasah heads makes a significant contribution to empowering teaching staff. (2) Organizing teaching staff with accountable standards and criteria makes it easier to distribute teaching staff evenly. (3) An appropriate implementation process can provide a positive impact in empowering teaching staff. (4) Routine and continuous supervision has an influence on the implementation process in a conducive manner. Based on the research results, it can be concluded that the systematic, accurate and accountable management of madrasah principals in empowering teaching staff can have a significant impact in minimizing the placement gap and equal distribution of State Madrasah Aliyah teaching staff in Jambi Province.